THE PRIORITY OF INTERNATIONAL FREIGHT EXPRESSES IN THE OVERLAPPING SECTION OF RFC 7 AND RFC 9 KOLÍN - CESKA TREBOVA - Přemysl Šrámek; Tatiana Molková (Acta Polytechnica CTU Proceedings, 2016)
This article deals with the railway traffic control and railway traffic equipment in terms of implementation of TSI. The main goal is to research the optimal priority of international freight expresses, especially in the overlapping sections, which represent critical line sections of European freight corridors. This article shows this problem in the context in the overlapping section of RFC 7 and RFC 9 Kolín – Ceská Trebová. There are mentioned possibilities of using of ETCS and implementation of automatic train paths.